HUBUNGAN PENGETAHUAN TENTANG FEKUNDABILITAS DAN SIKAP HIDUP SEHAT DENGAN PERILAKU REPRODUKSI SEHAT - Ning Setianti; Nadiroh Nadiroh (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2016)
The Objective of the research is to determine the relationship between the knowledge about fekundabilitas and healthy life style with healthy reproductive behavior in Depok.. The method which is used in this research is the correlation by survey research method. The technique of collected data using by test and non-tes with 80 respondents by multistage random sampling. The result of this research shows that the fekundabilitas knowledge and attitudes about healthy life style have a positive and significant relations with healthy reproductive behavior.